Optimizing electroporation assisted silver nanoparticle delivery into living C666 cells for surface-enhanced Raman spectroscopy. Issue 1 (2011) - Yu, Yun; Lin, Juqiang; Wu, Yanan; Feng, Shangyuan; Li, Yongzeng; Huang, Zufang; Chen, Rong; Zeng, Haishan
Abstract : Electroporation assisted metallic nanoparticle delivery has been shown by our previous work to significantly reduce the time of sample preparation for surface-enhanced Raman spectroscopy (SERS) measurements of biological cells. In this paper, we report our experimental work to optimize the electroporation parameters, including adjustment of the pulse pattern, operation temperature, and electroporation buffer, for fastest delivery of silver nanoparticles into living C666 cells (a human nasopharyngeal carcinoma cell line). The delivery efficiency was evaluated by the integrated intensity of whole cell SERS spectrum. Our work concluded that the silver nanoparticle delivery rate is best under the electroporation condition of using 4 consecutive 350 V (875 V/cm) rectangular electric pulses of 1, 10, 10 and 1 ms durations, respectively. Low temperature (0–4°C) is necessary for keeping cell viability during the electroporation process and it also improves the delivery efficiency of silver nanoparticles. The serum in the buffer has no obvious effect on the delivery efficiency.